De novo variant in tyrosine kinase SRC causes thrombocytopenia: case report of a second family. (3rd October 2019) - De Kock, Lore; Thys, Chantal; Downes, Kate; Duarte, Daniel; Megy, Karyn; Van Geet, Chris; Freson, Kathleen
Abstract: A germline heterozygous gain-of-function p .E527K variant in tyrosine kinase SRC was previously found to cause thrombocytopenia, myelofibrosis, bleeding, bone pathologies, premature edentulism and mild facial dysmorphia in nine patients of a single pedigree. Because of this variant, SRC loses its self-inhibitory capacity, causing constitutively active SRC expression in platelets. These patients have fewer and heterogeneous-sized platelets that are hyporeactive to collagen. We now report a 5-year-old girl with syndromic thrombocytopenia due to the same SRC-E527K variant that occurs de novo . A bone marrow biopsy, blood smear analysis, platelet aggregations, flow cytometric analysis of P -selectin, SRC expression and tyrosine phosphorylation studies were performed to confirm the similarities between the two families. This study strengthens our previous finding that hyperactive SRC kinase results in mild platelet dysfunction and thrombocytopenia with hypogranular platelets and further expands the clinical description of this syndrome to improve early recognition.